2021
DOI: 10.3390/ijms22158295
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Exosomal Regulations of Sepsis-Induced Metabolic Alterations

Abstract: Sepsis is a sustained systemic inflammatory condition involving multiple organ failures caused by dysregulated immune response to infections. Sepsis induces substantial changes in energy demands at the cellular level leading to metabolic reprogramming in immune cells and stromal cells. Although sepsis-associated organ dysfunction and mortality have been partly attributed to the initial acute hyperinflammation and immunosuppression precipitated by a dysfunction in innate and adaptive immune responses, the late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 131 publications
(157 reference statements)
0
9
0
Order By: Relevance
“…1 ). The cell membranes that are damaged under systemic hyperinflammatory conditions include those of the mitochondria with energy failure being commonplace in these diseased situations [ 79 ]. By inhibiting cyclooxygenase, melatonin attenuates the hyperinflammatory response that accompanies a SARS-CoV-2 infection [ 80 ].…”
Section: Melatonin/pla2 Interactionsmentioning
confidence: 99%
“…1 ). The cell membranes that are damaged under systemic hyperinflammatory conditions include those of the mitochondria with energy failure being commonplace in these diseased situations [ 79 ]. By inhibiting cyclooxygenase, melatonin attenuates the hyperinflammatory response that accompanies a SARS-CoV-2 infection [ 80 ].…”
Section: Melatonin/pla2 Interactionsmentioning
confidence: 99%
“…It may also be related to complex disorders of immune metabolism, which is one of the reasons that hinder the development of effective drugs for sepsis ( Weis et al, 2017 ; Koutroulis et al, 2019 ). In addition, disease tolerance is becoming a hub strategy for treating sepsis, and its mechanisms involve aspects such as immune metabolism, immune fitness, inflammation, and genetics ( Appiah et al, 2021 ). Relevant studies have shown that the innate and adaptive immune systems play an essential role in disease tolerance defense ( McCarville and Ayres, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“… 82 Proliferating endothelial cells display high levels of glycolysis even in the presence of oxygen, similar to the Warburg effect observed in tumour cells. 83 A similar metabolic shift in cancer vasculature can serve to explain changes in the metabolism of endothelial cells in sepsis. During tumour angiogenesis, lactate, the end‐product of glycolysis, activates NF‐κB by promoting the phosphorylation and degradation of the NF‐κB inhibitor IκB‐α.…”
Section: Neutrophils and Nets Induce A Pro‐inflammatory And Pro‐angio...mentioning
confidence: 99%